1989
DOI: 10.1039/c39890000560
|View full text |Cite
|
Sign up to set email alerts
|

Total and stereospecific synthesis of 2′-deoxycadeguomycin

Abstract: An efficient and stereospecific synthesis of 2'-deoxycadeguomycin (3) from the novel 7-deazapurine derivatives 2-amino-4-chloropyrrolo[2,3-dJpyrimidine-5-carbonitrile (10) or methyl 2-amino-4-chloropyrrolo[2,3-dJpyrimidine-5-carboxylate (12) has been accomplished.Cadeguomycin (1) is a novel nucleoside antibiotic isolated recently' from the culture broth of Streptomyces hygroscopicus IM7912T as a minor component together with tubercidin (4), and characterized as 2-amino-4-0~0-3,4-dihydro-7-P-~ribofuranosylpyrro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Since then, the 7deazapurine 2'-deoxyribonucleosides could be prepared in a stereo-controlled manner, with the exclusive formation of β-D-2'-deoxyribonucleosides [25,26]. Later on, this protocol was applied to the synthesis of other base-modified 2'deoxyribonucleosides [25,[28][29][30] as well as to 7-deazapurine ribonucleosides [31][32][33][34][35]. This was of particular value because the common glycosylation methods developed for purine nucleosides can not be applied efficiently to the synthesis of the corresponding 7-deazapurine nucleosides.…”
Section: General Comments On the Convergent Synthesis Of 7-deazapurinmentioning
confidence: 99%
“…Since then, the 7deazapurine 2'-deoxyribonucleosides could be prepared in a stereo-controlled manner, with the exclusive formation of β-D-2'-deoxyribonucleosides [25,26]. Later on, this protocol was applied to the synthesis of other base-modified 2'deoxyribonucleosides [25,[28][29][30] as well as to 7-deazapurine ribonucleosides [31][32][33][34][35]. This was of particular value because the common glycosylation methods developed for purine nucleosides can not be applied efficiently to the synthesis of the corresponding 7-deazapurine nucleosides.…”
Section: General Comments On the Convergent Synthesis Of 7-deazapurinmentioning
confidence: 99%
“…Amongst others this methodology [19][20][21] was applied to synthesize the multi-targeted antifolate Pemetrexed [22]. In the range of this reaction other working groups have observed the formation of interesting by-products [21,[23][24][25]. Already 1978 Secrist et al had found out that besides the pyrrolo [2,3d]pyrimidin-4-one derivative a furo[2,3-d]pyrimidine-2,4diamine was formed [21].…”
Section: Resultsmentioning
confidence: 99%
“…In 1984 Robins and Kazimierczuk used NaH to generate the nucleobase anion with MeCN as solvent and employed the sugar halide 6 in the glycosylation reaction [33]. This method was applied to the synthesis of a number of 7-dezapurine 2'-deoxyribonucleosides, such as 7-deaza-2'-deoxyguanosine (11a), its derivatives 11d, 11g, 11h, 11j [84][85][86][87], and related to 2'-deoxytubercidin derivatives 13a, 13f, 13j, 17f, 20, 37a, and 60-66 (Scheme 28) [33,34,[88][89][90].…”
Section: Nucleobase Anion Glycosylation -Sodium Salt Proceduresmentioning
confidence: 99%
“…The synthesis of 2'-deoxycadeguomycin made by the sodium salt procedure is shown in Scheme 33 [85,93] which was converted to 7-nitro-7-deazapurine 87. Compound 87 was glycosylated with 2-deoxy-3,5-di-O-(p-chlorobenzoyl)--D-erythro-pentofuranosyl chloride (88) in DMF in the presence of NaH resulting in -D-nucleoside 89.…”
Section: Nucleobase Anion Glycosylation -Sodium Salt Proceduresmentioning
confidence: 99%